Fault Injection Attacks on Cryptographic Devices: Theory, Practice, and Countermeasures - Barenghi, Alessandro; Breveglieri, Luca; Koren, Israel; Naccache, David (Proceedings of the IEEE, 2012)
Implementations of cryptographic algorithms continue to proliferate in consumer products due to the increasing demand for secure transmission of confidential information. Although the current standard cryptographic algorithms proved to withstand exhaustive attacks, their hardware and software implementations have exhibited vulnerabilities to side channel attacks, e.g., power analysis and fault injection attacks. This paper focuses on fault injection attacks that have been shown to require inexpensive equipment and a short amount of time. The paper provides a comprehensive description of these attacks on cryptographic devices and the countermeasures that have been developed against them. After a brief review of the widely used cryptographic algorithms, we classify the currently known fault injection attacks into low-cost ones (which a single attacker with a modest budget can mount) and high-cost ones (requiring highly skilled attackers with a large budget). We then list the attacks that have been developed for the important and commonly used ciphers and indicate which ones have been successfully used in practice. The known countermeasures against the previously described fault injection attacks are then presented, including intrusion detection and fault detection. We conclude the survey with a discussion on the interaction between fault injection attacks (and the corresponding countermeasures) and power analysis attacks.